Difference in Pregnancy Related Stress Levels Between Primigravida and Multigravida Women - Novi Maulidiyah; Dyah Widodo; Heny Astutik; Ika Yudianti (Jurnal Kesehatan Ibu dan Anak, 2026)
Pregnancy is a physiological process accompanied by physical, hormonal, and psychological changes that may trigger pregnancy-related stress. Maternal stress during pregnancy can disrupt hormonal balance, reduce immune function, adversely affect fetal development, and increase the risk of pregnancy complications. This study aimed to pregnancy-related stress level between primigravida and multigravida women attending a primary healthcare center in Malang City, Indonesia. This quantitative study employed a comparative cross-sectional design. The study was conducted at Janti Public Health Center, Sukun District, Malang City, from May–June 2025 among 64 pregnant women, comprising 32 primigravidas and 32 multigravidas, selected using purposive sampling. The inclusion criteria were primigravida and multigravida pregnant women with low-risk pregnancies who could operate mobile phones, while the exclusion criteria were pregnant women who received psychological therapy. Pregnancy-related stress were measured using the Pregnancy Stress Rating Scale (PSRS-36) and analyzed using the Mann-Whitney test (α = 0.05). The results showed that most primigravida experienced moderate (37.5%) and high (31.2%) levels of pregnancy-related stress, while multigravida were predominantly moderate (62.5%). There was a significant difference between the two groups (p = 0.046) with an average level of pregnancy-related stress in primigravida of 36.80 higher than in multigravida of 28.20. This study shows levels of pregnancy-related stress in primigravida mothers are higher than those in multigravida mothers, confirming that previous pregnancy experiences play a role in maternal psychological adaptation. These findings contribute to the understanding of pregnancy-related stress in the context of primary healthcare in Indonesia. Therefore, integrating pregnancy-related stress screening into routine antenatal care, as well as providing education and family support for first-time pregnant women, should be considered as strategies for early detection and management of pregnancy-related stress during pregnancy.